Evaporation in Capillary Porous Media at the Perfect Piston‐Like Invasion Limit: Evidence of Nonlocal Equilibrium Effects. Issue 12 (13th December 2017) - Attari Moghaddam, Alireza; Prat, Marc; Tsotsas, Evangelos; Kharaghani, Abdolreza
Abstract: The classical continuum modeling of evaporation in capillary porous media is revisited from pore network simulations of the evaporation process. The computed moisture diffusivity is characterized by a minimum corresponding to the transition between liquid and vapor transport mechanisms confirming previous interpretations. Also the study suggests an explanation for the scattering generally observed in the moisture diffusivity obtained from experimental data. The pore network simulations indicate a noticeable nonlocal equilibrium effect leading to a new interpretation of the vapor pressure‐saturation relationship classically introduced to obtain the one‐equation continuum model of evaporation. The latter should not be understood as a desorption isotherm as classically considered but rather as a signature of a nonlocal equilibrium effect. The main outcome of this study is therefore that nonlocal equilibrium two‐equation model must be considered for improving the continuum modeling of evaporation. Key Points: The classical continuum modeling of evaporation in capillary porous media is revisited from pore network simulations The moisture diffusivity is characterized by a minimum corresponding to the transition between liquid and vapor transport mechanisms The pore network simulations indicate a noticeable nonlocal equilibrium effect